(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
Cash management, in general, is one of the most important matters that management should follow up, due to its effective role and importance in improving the financial performance of companies. The research aims to measure and know the impact of free cash flow on the market value of business establishments. A modern measure of their financial performance by mentioning its data in a special list like the rest of the lists. The research came to show the impact of free cash flow on the market value of business establishments by demonstrating the importance of using free cash flow indicators in industrial companies listed in the Iraq Stock Exchange by conducting an applied study that seeks to reach a predictive model for the market value of these companies, and represents the research community in industrial companies. Listed in the Iraq Stock Exchange, and the research sample was represented in (6) companies that were selected from among (19) companies listed in the Iraq Stock Exchange, due to their compatibility with the research requirements and the period from (2004-2019), and a set of indicators were used. Financial [earnings before taxes and interest (1-tax) + amortization and depreciation - capital expenses), (closing price multiplied by the number of shares)] as well as using a simple regression model to find out the effect of the independent variable on the dependent variable individually and for each company and using the statistical program ( Minitab 17), and the research concluded that there is a statistically significant effect of free cash flow on the market value of business establishments in general in the model, as well as that there is no effect of free cash flow on the market value Protective for business establishments in some companies.